POST MERGER NOTIFICATION DAN KONSEKUENSI KETERLAMBATAN DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA - Pawiring, Meisyani Putri Ayu Angela; Muryanto, Yudho Taruno (Fakultas Hukum Universitas Sebelas Maret, 2026)
The obligation to provide notification or notification for business entities that carry out Merger, Consolidation or Acquisition has been regulated in the system of laws and regulations. In Indonesia itself, using the mandaroty post-merger notification approach. The purpose of the notification is to prevent monopolistic practices and unfair business competition. This article aims to find out how the post notification merger process in Indonesia and the consequences when business entities are late in carrying out notification obligations using normative legal research with a conceptual approach using legal materials including primary and secondary legal materials, data collection techniques in the form of library research. The results show that although there are two types of notifications, what is required for business entities is only post-merger notification, while pre-merger notification is only voluntary. Business entities may be subject to a fine of Rp. 1,000,000,000 (one billion rupiah) per day of delay with a maximum of Rp. 25,000,000,000 (twenty five billion rupiah) as updated in the Job Creation Law, the maximum fine being Rp.2,000,000,000 (two billion rupiah)